2022
DOI: 10.1111/anae.15942
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of intravenous dexmedetomidine added to dexamethasone for arthroscopic rotator cuff repair and duration of interscalene block

Abstract: Prolongation of peripheral nerve blockade by intravenous dexamethasone may be extended by intravenous dexmedetomidine. We randomly allocated 122 participants who had intravenous dexamethasone 0.15 mg.kg À1 before interscalene brachial plexus block for day-case arthroscopic rotator cuff repair to intravenous saline (62 participants) or intravenous dexmedetomidine 1 lg.kg À1 (60 participants). The primary outcome was time from block to first oral morphine intake during the first 48 postoperative hours. Fifty-nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Two later trials were not able to reproduce these findings using a similar protocol and population. 13,14 In accordance with our results, both showed that the combination of the dexamethasone and dexmedetomidine did not increase the duration of analgesia significantly when compared with dexamethasone alone. These trials also used time to first pain as the definition of the duration of analgesia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Two later trials were not able to reproduce these findings using a similar protocol and population. 13,14 In accordance with our results, both showed that the combination of the dexamethasone and dexmedetomidine did not increase the duration of analgesia significantly when compared with dexamethasone alone. These trials also used time to first pain as the definition of the duration of analgesia.…”
Section: Discussionsupporting
confidence: 92%
“…17 Notably, in three trials performing brachial plexus blocks and in one trial investigating combined sciatic, femoral, obturator, and lateral femoral cutaneous nerve blocks, the duration of analgesia was between 22.5 h and 29.5 h with dexamethasone and dexmedetomidine, which was not a consistent increase from dexamethasone alone. 13,14,18,19 We believe the cumulative evidence currently suggests that combined dexamethasone and dexmedetomidine provides a similar duration of analgesia as dexamethasone alone. Therefore, it appears reasonable to use dexamethasone as the sole adjunct to a peripheral nerve block if the goal is to increase the duration of analgesia.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, intravenous dexmedetomidine was not demonstrated to be provide any clinical benefit to local anaesthetic alone, suggesting a solely perineural mechanism of action for this local anaesthetic adjunct as has been evidenced by previous animal [39] and human studies [40]. Consistent with this, a randomized controlled trial found that intravenous dexamethasone and dexmedetomidine were not superior to dexamethasone alone in brachial plexus block for duration of sensory and motor blockade and the duration of analgesia as well as the pain score at rest and on movement and cumulative oral morphine consumption [41]. Further, these results revealed that unlike perineural and intravenous dexmedetomidine, perineural and intravenous dexamethasone have the potential to prolong sensory blockade to a greater extent than motor blockade [38 ▪▪ ].…”
Section: Intravenous Versus Perineural Local Anaesthetic Adjunctsmentioning
confidence: 52%
“…However, it may cause bradycardia and hypotension, and it has a slow onset when used as a single sedative. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%